2015
DOI: 10.1111/jcmm.12581
|View full text |Cite
|
Sign up to set email alerts
|

Functional abnormalities in iPSC‐derived cardiomyocytes generated from CPVT1 and CPVT2 patients carrying ryanodine or calsequestrin mutations

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited arrhythmia characterized by syncope and sudden death occurring during exercise or acute emotion. CPVT is caused by abnormal intracellular Ca2+ handling resulting from mutations in the RyR2 or CASQ2 genes. Because CASQ2 and RyR2 are involved in different aspects of the excitation-contraction coupling process, we hypothesized that these mutations are associated with different functional and intracellular Ca²+ abnormalities. To test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 40 publications
(86 reference statements)
15
61
0
Order By: Relevance
“…Subsequently, many hiPSC-CMs models of both CPVT types [20][21][22][23][24][25][26][27][28][29] were shown to recapitulate the clinical phenotype in the culture-dish by displaying abnormal Ca 2+ handling and arrhythmias. Here, we focused on CPVT2 and found, similar to previous reports, 24,25,29 21,30 We recently investigated this phenomenon in a CPVT1-hiPSC-CMs model demonstrating a reduced SOICR threshold in the affected cells. 21 Here, we demonstrated the ability to model SOICR also in the CPVT2-hiPSC-CMs and revealed that the D307H-CASQ2 may also reduce SOICR threshold in the affected cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, many hiPSC-CMs models of both CPVT types [20][21][22][23][24][25][26][27][28][29] were shown to recapitulate the clinical phenotype in the culture-dish by displaying abnormal Ca 2+ handling and arrhythmias. Here, we focused on CPVT2 and found, similar to previous reports, 24,25,29 21,30 We recently investigated this phenomenon in a CPVT1-hiPSC-CMs model demonstrating a reduced SOICR threshold in the affected cells. 21 Here, we demonstrated the ability to model SOICR also in the CPVT2-hiPSC-CMs and revealed that the D307H-CASQ2 may also reduce SOICR threshold in the affected cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In the cardiac field, hiPSCs were established from healthy individuals and from patients inflicted with acquired 9 and several types of inherited cardiac disorders. 10,11 Patient-specific hiPSC-derived cardiomyocyte (hiPSC-CM) models of different inherited arrhythmogenic syndromes (including the long-QT, [12][13][14][15] Brugada, 16 and sodium channel overlap 17 syndromes; arrhythmogenic right ventricular cardiomyopathy 18,19 ; and both types of CPVT [20][21][22][23][24][25][26][27][28][29] ) were…”
Section: See Editorial By LI Et Almentioning
confidence: 99%
“…This supported the mechanistic explanation that increased diastolic Ca 2ϩ can lead to the development of arrhythmias. In a separate study, ultrastructural characterization demonstrated that hiPSC-CMs from CPVT1 patients also have enlarged mitochondrial, glycogen, and lysosome clusters, as well as thinner Z-bands, reduced number of sarcomeres per cell, and increased sarcomere disarray (206). These phenotypes were more pronounced in CPVT2 hiPSC-CMs, demonstrating that hiPSCs provide a setting for the investigation of the similarities and differences in the pathophysiological consequences of different mutations.…”
Section: A Cardiac Channelopathiesmentioning
confidence: 97%
“…Liu et al have reported a facilitated maturation of Ca 2+ handling properties of transgenic hES-CMs with CSQ overexpression. CSQ is a high-capacity but low affinity Ca 2+ binding protein in the SR, playing an important role in regulating excitation-contraction coupling and CICR in the heart [16, 30-31]. It serves as a major Ca 2+ buffer that modulate RyR activity through Jn and Trd, and also as a reservoir for Ca 2+ readily accessible for CICR [31].…”
Section: Discussionmentioning
confidence: 99%